Poly[dimethanolbis[μ-5-(3-pyridyl)tetrazolato-κ(2) N (2):N (5)]copper(II)] - Wei, Xiao-Hong (International Union of Crystallography, 2010)
In the crystal structure of the title complex, [Cu(C(6)H(4)N(5))(2)(CH(3)OH)(2)](n), the Cu(II) cation lies on an inversion center and is coordinated by four 5-(3-pyridyl)tetrazolate anions and two methanol molecules in an elongated distorted CuN(4)O(2) octahedral geometry. Each 5-(3-pyridyl)tetrazolate anion bridges two Cu(II) cations, forming a two-dimensional polymeric complex with (4,4) network topology. In the crystal structure, the two-dimensional layers are connected by intermolecular O—H⋯N hydrogen bonding, forming a three-dimensional supramolecular architecture.